THE ROLE OF THE MANAGER OF THE COMMUNITY LEARNING ACTIVITY CENTER BINTANG CENDIKIA ANANDA IN IMPROVING READING CULTURAL LITERACY THROUGH TAMAN BACAAN MASYARAKAT - Dini Palma Yuliana; Reta Meliyani; Winika Atalia BR Sitepu; Abellia Marsyanda (Journal Education for All: Media Informasi Ilmiah Bidang Pendidikan Luar Sekolah, 2026)
The low reading interest of the Indonesian people is a challenge in efforts to strengthen literacy, so the role of non-formal educational institutions such as Community Reading Centers (PKBM) is needed. This study aims to describe the role of the management of PKBM Bintang Cendikia Ananda in improving literacy reading culture through Community Reading Gardens (TBM). The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The results show that PKBM managers play an active role in providing literacy facilities, organizing writing and reading activities, and building collaborations with various parties to support literacy programs. Managers also apply a personal approach and ongoing mentoring that can increase community motivation and confidence in reading and writing. Although there are obstacles such as low self-confidence of some participants, the strategies implemented by managers have proven effective in fostering a culture of literacy. Thus, TBM PKBM Bintang Cendikia Ananda functions not only as a reading space, but also as a center for literacy-based community empowerment